Opportunities and challenges for antisense oligonucleotide therapies. Issue 1 (3rd June 2020) - Kuijper, Elsa C.; Bergsma, Atze J.; Pijnappel, W.W.M. Pim; Aartsma‐Rus, Annemieke
Abstract: Antisense oligonucleotide (AON) therapies involve short strands of modified nucleotides that target RNA in a sequence‐specific manner, inducing targeted protein knockdown or restoration. Currently, 10 AON therapies have been approved in the United States and Europe. Nucleotides are chemically modified to protect AONs from degradation, enhance bioavailability and increase RNA affinity. Whereas single stranded AONs can efficiently be delivered systemically, delivery of double stranded AONs requires capsulation in lipid nanoparticles or binding to a conjugate as the uptake enhancing backbone is hidden in this conformation. With improved chemistry, delivery vehicles and conjugates, doses can be lowered, thereby reducing the risk and occurrence of side effects. AONs can be used to knockdown or restore levels of protein. Knockdown can be achieved by single stranded or double stranded AONs binding the RNA transcript and activating RNaseH‐mediated and RISC‐mediated degradation respectively. Transcript binding by AONs can also prevent translation, hence reducing protein levels. For protein restoration, single stranded AONs are used to modulate pre‐mRNA splicing and either include or skip an exon to restore protein production. Intervening at a genetic level, AONs provide therapeutic options for inherited metabolic diseases as well. This review provides an overview of the different AON approaches, with a focus on AONs developed for inborn errors of metabolism.